1999
DOI: 10.1128/jvi.73.4.2596-2603.1999
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cell Tropism of Feline Immunodeficiency Virus Molecular Clones In Vivo

Abstract: Independent studies have demonstrated different cell tropisms for molecular clones of feline immunodeficiency virus (FIV). In this report, we examined three clones, FIV-pF34, FIV-14, and FIV-pPPR, for replication in Crandell feline kidney (CrFK) cells, feline peripheral blood mononuclear cells (PBMC), and feline macrophage cultures. Importantly, cell tropism for these three clones was also examined in vivo. FIV-pF34 replication was efficient in CrFK cells but severely restricted in PBMC, whereas replication of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…[4][5][6][7]10,11,21,[190][191][192][193][194] Early studies revealed that targets for FIV in vitro and in vivo included CD4 T-cells, macrophages, dendritic cells, microglia, and astrocytes similar to those for HIV infection in humans, but also included CD8 T-cells, and B-cells (Table II). 4,18,23,186,[195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210] Early reports also demonstrated that continuous passage of particular FIV isolates in cell culture selected for virus variants capable of replication in feline adherent cell lines, including Crandell feline kidney cells (CrFK) and G355-5 cells, as well as established feline interleukin (IL)-2-independent T-cell lines. 2,25,42,211 Importantly, experimental inoculation studies in cats revealed that cell culture-adapted viruses represented a particular subset of viral variants that exhibited reduced replication and virulence in vivo.…”
Section: Fiv Receptor Usagementioning
confidence: 99%
See 4 more Smart Citations
“…[4][5][6][7]10,11,21,[190][191][192][193][194] Early studies revealed that targets for FIV in vitro and in vivo included CD4 T-cells, macrophages, dendritic cells, microglia, and astrocytes similar to those for HIV infection in humans, but also included CD8 T-cells, and B-cells (Table II). 4,18,23,186,[195][196][197][198][199][200][201][202][203][204][205][206][207][208][209][210] Early reports also demonstrated that continuous passage of particular FIV isolates in cell culture selected for virus variants capable of replication in feline adherent cell lines, including Crandell feline kidney cells (CrFK) and G355-5 cells, as well as established feline interleukin (IL)-2-independent T-cell lines. 2,25,42,211 Importantly, experimental inoculation studies in cats revealed that cell culture-adapted viruses represented a particular subset of viral variants that exhibited reduced replication and virulence in vivo.…”
Section: Fiv Receptor Usagementioning
confidence: 99%
“…2,25,42,211 Importantly, experimental inoculation studies in cats revealed that cell culture-adapted viruses represented a particular subset of viral variants that exhibited reduced replication and virulence in vivo. 111,192,197,212 FIV infection of feline CD4-negative adherent cell lines provided indirect evidence that FIV differs with HIV-1 and does not utilize CD4 as a primary receptor. In addition, direct evidence refuting FIV usage of CD4 was provided by studies revealing an absence of virus infectivity for nonlymphoid cells expressing feline CD4.…”
Section: Fiv Receptor Usagementioning
confidence: 99%
See 3 more Smart Citations